PHYSICAL ACTIVITY, FUNCTIONAL CAPACITY AND QUALITY OF LIFE IN OLDER PEOPLE - Bravo, Jorge (2012)
Gerontological research has shown that there is a marked decline in health with age and an associated demand for expensive medical services (Shepard, 1993). Some previous studies underline sedentary lifestyle as main responsible factor for hypokinetic diseases and reduction in quality of life (Rejeski et al, 1996). By contrast, among the elderly evidences show a positive relationship between regular physical activity and a high physical fitness on reduction of anxiety and depression levels, improving older peopleʼs quality of life (ACSM, 1998, 2000; Blair et al, 1995). Otherwise, the acquisition and maintenance of motor skills are critical to the preservation of an independent lifestyle and quality of life in the elderly (Rikli and Edwards, 1991). The aim of the present study was to evaluate the relationship between physical activity levels, physical fitness and quality of life among institutionalized and non-institutionalized older people. • Older people with institutional community dwelling had lower physical activity levels than non-institutionalized similar individuals. • Physical activity influences older people's functional capacity especially aerobic capacity, and quality of life in several domains. • The above results suggest that caring elderly in their own homes seems to provide higher activity patterns, functional capacities and quality of life.